Ethylmalonic aciduria - Youssef, N. (1994)
Five infants from 3 families, one Egyptian, two Yemeni, are described with a progressive encephalopathy, four of whom have been studied in detail. All patients showed vascular lesions of the skin, characterized by waxing and waning petechiae and ecchymoses. Acrocyanosis was present in three patients. All patients showed retinal lesions characterized by tortuous veins. Protracted diarrhea was not a consistent finding, although they had metabolic crisis in association with diarrhea. They did not show failure to thrive. The neurologic symptoms were indicative of a progressive pyramidal tract disease. Three patients died following sudden emergence of severe basal ganglia, putaminal and head of caudate lesions. In one patient the CT changes in brain were suggestive of infarction. The patients who died manifested pulmonary congestion, or wet lung, and respiratory difficulties during the terminal stage of the disease. In all patients before and during the terminal event, mild-to-moderate hematuria, and in two RBC in CSF, was observed. In one patient there was mild hemoperitoneum at the terminal event. The urine organic acids indicated increased excretion of ethylmalonic, methylsuccinic, glutaric, and adipic acids. The patients invariably showed lactic acidosis, but no ketosis, during and in between the acidotic attacks of the disease. The acylcarnitine profile in blood of two patients showed a pronounced increase in C4 and C5 carnitine esters. In three patients, biopsies from petechiae indicated absence of an immune event, showing only fresh hemorrhage. An immunologic study in one patient was normal for the suppressor: cytotoxic lymphocyte ratio and concentration of interleukin-2 receptor during and in between hemorrhagic attacks. The cytochrome c oxidase activity in fibroblasts was normal. The rate of oxidation of glucose, leucine, isoleucine, valine, propionate and butyrate by fibroblasts was normal. The disease is not responsive to treatment with riboflavin, ascorbic acid, vitamin E, glycine, or carnitine. One patient remained stable on prolonged large doses of methylprednisolone. The biochemical defect leading to ethylmalonic aciduria in this disease remains unknown.